THE EFFECT OF THE USE OF LETTER PUZZLE MEDIA ON THE READING ABILITY OF GRADE I STUDENTS OF SDN KARANGTENGAH PRANDON 2 NGAWI - Dilla Istighfar Risqi; Budi Sasomo; Uci Ulfa Nur'afifah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
In reading learning, it is shown that there are various difficulties experienced by grade I students of SDN Karangtengah Prandon2 Ngawi in reading, including inability to recognize letters, the absence or replacement of letters when reading, difficulties in reading word by word, and difficulties in distinguishing vowels and consonants. In addition, students also experience obstacles in combining letters and syllables into whole words, and pay less attention to the use of punctuation. These difficulty factors include low interest in learning to read, lack of motivation when participating in reading activities, The type of research used is using a quantitative approach with the Pre-Experimental Design type. The researcher used the One Group Pretest-Posttest Design research design to be carried out in one class without a comparison class using a pretest before being given treatment. With that, the results of the treatment can be known more accurately, because it can be compared with the situation before being given treatment. The results of this study are that there is a significant influence of the use of Letter Puzzle media on the reading ability of grade I students of SDN Karangtengah Prandon 2 Ngawi.